PENGARUH PROMOSI DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO JAFAR PLAZA BANGUNAN AEK TOLANG KABUPATEN TAPANULI TENGAH - Bariq Direza Manik; Yacub Hutabarat; Nelly A. Sinaga (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to determine the effect of promotion and trust on purchasing decisions at the Jafar Plaza Store, Aek Tolang Building, Central Tapanuli Regency. The type of research used in this study is a quantitative descriptive research type, because this research method aims to obtain information by creating a picture or description of what exists or is happening. This research was conducted from April to August 2024. For this study, the population was 200 people taken from all consumers who made purchases on average every week. Then, the author took 25% of the population to be used as a sample, namely 50 people. The type of data used in this thesis research is the type of subject data and the data source is primary. From the results of the instrument test, valid and reliable results were obtained because all questions contained in variables X1, X2 and Y have a Corrected Item-Total Correlation value, greater than 0.300 and a Cronbach's Alpha value, each variable above 0.60 which means all questions are valid. and reliability. From the results of the data testing, an influence of 70.4% was obtained, this means that what happened to the variation of the dependent variable was 70.4% determined by the independent variable. From the hypothesis test, the results of the calculated t value <t table and the calculated F value> F table, so the hypothesis proposed in this study can be accepted. .